The Influence of the NHT Assisted Media Model and Learning Motivation on Learning Outcomes of Citizenship Education - Fauziah Nasution; Deny Setiawan; Wildansyah Lubis (Britain International for Academic Research (BIAR) Publisher, 2020)
The aim of this research is to know the influence of NHT assisted media model and learning motivation on learning outcomes of citizenship education. This research will be implemented in 5th grade of Primary School at SD IT Tahfizhil Quran YIC SU, which is located at Jalan Haji Hospital. This school has an